A DYNAMICAL INVESTIGATION OF THE HEAT AND HELIUM IMBALANCE - van Keken P.E.; Ballentine C.J.; Porcelli D. (My University, 2001)
The terrestrial heat-helium imbalance [O'Nions and Oxburgh, Nature 306 (1983) 429-431] is based on the observation that significantly less 4He is released from the Earth's mantle than is predicted from the radiogenic element budget and observed heat flow. We review recent observations and models of Earth's radioelement distribution and 4He flux and demonstrate that this imbalance remains a robust observation. We explore the hypothesis that the imbalance can be accounted for by different timescales of heat and helium extraction from the mantle system. This is tested using dynamical models of mantle convection that incorporate thermal evolution, helium ingrowth and degassing. The temporal decoupling of heat and helium loss provides large excursions from the mantle heat and helium production ratio and can indeed drop to values as low as those observed. Nevertheless, the duration of these periods is very limited within the 4 Byr model period and the probability that the present-day situation is caused by such an excursion must be considered to be very small. While the average ratio of heat and helium released from the whole mantle convection models is smaller than the production ratio, a significant imbalance remains. An additional mechanism is required to further separate heat from helium.
Keywords: MANTLE; CONVECTION; RADIOACTIVE ISOTOPES; HEAT FLOW; DEGASSING; NOBLE GASES